Examining Varying Rainfall in the different elevation of Nepal and Water Scarcity - Bista, Raghu Bir; Thakuri, Sudeep; Koirala, Prakirti; Bhattarai, Arun (Economic Journal of Development Issues, 2023)
This study assesses the variation of rainfall in the different elevations in the water basin in Nepal. Employing time series data sets of rainfall from 1980 to 2020 collected from Department of Hydrology and Metrology, Nepal, this study has used Mann Kendal test and Sen’s test. In the different elevations, the variation of rainfall is heterogeneous. In the steep elevated landscapes, rainfall is extreme. In the last 47 years, trend of annual rainfall’s mean (Rmean) and moving average (Rmeanma) have been declining. During that period, there were extremes of higher and lower rainfall in the decadal time frame. Kendall’s coefficient (τ) and Sen’s coefficient (β) of Rmean are -3.65°c and -0.13°c respectively. It implies decreasing trend of Rmean from 1975 to 2020. Sen’s coefficient (β) of Rmean validate decreasing trend of Rmean. However, it is insignificant (P=0.2>0.05). Differently, except Kendall’s coefficient (τ) and Sen’s coefficient (β) of Rmean in Tzone2 (1990-1999), Kendall’s coefficient (τ) and Sen’s coefficient (β) of the remaining three time zones, Tzone1 (1980-1989), Tzone3 (2000-2009) and Tzone4 (2010-2019) are negative. Therefore, rainfall has negative trend in the different elevations of the water basin. We conclude water scarcity & stress exist in the small cities. To minimize water vulnerability, water saving and preserving behaviour of household should be developed and the government agency should campaign tree plantation, protect water sources and initiate water management program.